Rhetoric in popular culture - Brummett, Barry 1951- (Thousand Oaks, California SAGE, 2023)
The Sixth Edition of Barry Brummett’s Rhetoric in Popular Culture provides readers with in-depth insight into the techniques of rhetorical criticism to analyze the full spectrum of contemporary issues in popular culture. Exploring a wide range of mass media texts including advertisements, magazines, movies, television, popular music, and social media, Barry Brummett presents key rhetorical concepts and applies them with critical analysis to a variety of exciting examples drawn from today's popular culture. Ideal for courses in rhetorical criticism, the new edition includes new and updated sample critical essays and case studies that demonstrate for readers how the critical methods discussed can be used to study the hidden rhetoric of popular culture.
Chapter 1. Rhetoric and the Rhetorical Tradition -- Chapter 2. Rhetoric and Popular Culture -- Chapter 3. Rhetorical Methods in Critical Studies -- Chapter 4. Varieties of Rhetorical Criticism: INTERVENTION-Understanding -- Chapter 5. Varieties of Rhetorical Criticism: UNDERSTANDING-Intervention -- Chapter 6. Paradoxes of Personalization: Race Relations in Milwaukee -- Chapter 7. Notes from a Texas Gun Show -- Chapter 8. Simulational Selves, Simulational Culture in Groundhog Day -- Chapter 9. Jumping Scale in Steampunk: One Gear Makes You Larger, One Duct Makes You Small -- Chapter 10. The Bad Resurrection in American Life and Culture.
Includes bibliographical references (pages 311-327) and index.
Keywords: Rhetoric; Popular culture; Rhetorical criticism